Gain-of-function variants in NLRP1 protect against the development of diabetic kidney disease NLRP1 inflammasome role in metabolic stress sensing? - Soares, Jaine L S (Clinical immunology (Orlando, Fla.), 2018)
Copyright © 2017 Elsevier Inc. All rights reserved.